Vínculos entre el estado de conservación de vegetación ribereña y las comunidades de diatomeas epilíticas como bioindicadores de calidad de agua en el río Malacatos de la ciudad de Loja. - Yaguana Neira, Roberth Ivan (2022)
This research analyzed the effects of the conservation status of riparian vegetation on the physical-chemical conditions of the water, as well as on the richness, diversity and biovolume of epilithic diatom communities in the Malacatos River. Three sections of the study were determined: riverbanks with native vegetation, banks with altered (semi-conserved) vegetation, and a section without riverside vegetation (urban area). For each zone, five repetitions were performed where samples were taken from substrates (small stones) for the biological analysis of diatom cells. Data on pH, total dissolved solids and temperature were taken from the water column, while turbidity and concentrations of phosphates and nitrates were measured at the laboratory. Twenty-one genera of diatoms (4765 individuals) were identified, the highest richness was recorded in the urban section (17 genera). Diversity obtained moderate values (≥ 2) in the native and semi-conserved areas. The highest cell biovolume was obtained in the native zone (1.32 x 1010 um3/ml). The genera Cymbella, Sellaphora, Nitzschia, Navicula, Ulnaria, Frustulia and Gomphonema presented greater abundance in the urban section where the water reflected a relatively alkaline pH level, as well as high values of total dissolved solids, temperature and phosphates. In the native and semi-conserved area, the genera Hannaea, Psammothidium, Achnanthes, Pinnularia, Eunotia and Cocconeis were negatively related to high concentrations of metrics such as pH, total dissolved solids, temperature and phosphates. The ecological conditions determined values of trophic state between eutrophic levels for the native and semi-preserved areas, up to hypereutrophic levels in areas without riparian vegetation. Keywords: epilithic diatoms, riparian vegetation, richness, diversity, biovolume